Metabolomics reveals metabolite changes of patients with pulmonary arterial hypertension in China. Issue 4 (16th January 2020) - Chen, Chenyang; Luo, Fei; Wu, Panyun; Huang, Yiyuan; Das, Avash; Chen, Shenglan; Chen, Jingyuan; Hu, Xinqun; Li, Fei; Fang, Zhenfei; Zhou, Shenhua
Abstract: The specific mechanism of pulmonary arterial hypertension (PAH) remains elusive. The present study aimed to explore the underlying mechanism of PAH through the identity of novel biomarkers for PAH using metabolomics approach. Serum samples from 40 patients with idiopathic PAH (IPAH), 20 patients with congenital heart disease‐associated PAH (CHD‐PAH) and 20 healthy controls were collected and analysed by ultra‐high‐performance liquid chromatography coupled with high‐resolution mass spectrometry (UPLC‐HRMS). Orthogonal partial least square‐discriminate analysis (OPLS‐DA) was applied to screen potential biomarkers. These results were validated in monocrotaline (MCT)‐induced PAH rat model. The OPLS‐DA model was successful in screening distinct metabolite signatures which distinguished IPAH and CHD‐PAH patients from healthy controls, respectively (26 and 15 metabolites). Unbiased analysis from OPLS‐DA identified 31 metabolites from PAH patients which were differentially regulated compared to the healthy controls. Our analysis showed dysregulation of the different metabolic pathways, including lipid metabolism, glucose metabolism, amino acid metabolism and phospholipid metabolism pathways in PAH patients compared to their healthy counterpart. Among these metabolites from dysregulated metabolic pathways, a panel of metabolites from lipid metabolism and fatty acid oxidation (lysophosphatidylcholine, phosphatidylcholine, perillic acid, palmitoleic acid, N‐acetylcholine‐d ‐sphingomyelin, oleic acid, palmitic acid and 2‐Octenoylcarnitine metabolites) were found to have a close association with PAH. The results from the analysis of both real‐time quantitative PCR and Western blot showed that expression of LDHA, CD36, FASN, PDK1 GLUT1 and CPT‐1 in right heart/lung were significantly up‐regulated in MCT group than the control group.